2022
DOI: 10.3389/fendo.2022.1020655
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative red cell distribution width is associated with postoperative lymphovascular invasion in prostate cancer patients treated with radical prostatectomy: A retrospective study

Abstract: PurposeTo investigate the relationship between baseline clinicopathological and laboratory variables especially hematological parameters and lymphovascular invasion (LVI) in patients who underwent radical prostatectomy (RP).MethodsWe retrospectively evaluated 348 prostate cancer (PCa) patients who underwent RP in our center between May 2018 and June 2021. We divided them into non-LVI and LVI groups based on LVI status, and compared clinicopathological characteristics between non-LVI and LVI groups. Clinicopath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“…This approach holds the potential to enhance risk stratification and further refine therapeutic decisionmaking in PCa management. The logistic regression identified preoperative PSA, PPBC, and GGG as robust predictors of LVI, consistent with findings from previous studies (5,15,(25)(26)(27)(28)(29)(30)(31)(32). Notably, we also identified MRI-based cT as a significant predictor of LVI, a factor not previously described in the literature to the best of our knowledge.…”
Section: Discussionsupporting
confidence: 91%
“…This approach holds the potential to enhance risk stratification and further refine therapeutic decisionmaking in PCa management. The logistic regression identified preoperative PSA, PPBC, and GGG as robust predictors of LVI, consistent with findings from previous studies (5,15,(25)(26)(27)(28)(29)(30)(31)(32). Notably, we also identified MRI-based cT as a significant predictor of LVI, a factor not previously described in the literature to the best of our knowledge.…”
Section: Discussionsupporting
confidence: 91%
“…The existing body of research has established various associations between hematological parameters and PCa, highlighting the potential of these indicators in understanding disease progression and prognosis. Wang F et al demonstrated a signi cant correlation between preoperative red cell distribution width (RDW) and lymphovascular invasion in PCa, suggesting RDW's importance in the disease's advancement (Wang et al 2022). Similarly, Albayrak et al found RDW to be predictive of an increased risk of PCa, further underscoring its role in disease progression (Albayrak et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…One study [10] included 79 PCa patients, although the exact number of LVI-positive patients was not disclosed. Of thirty-nine included papers, seventeen were retrospective and single-center [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27], twelve were retrospective and multi-center [28][29][30][31][32][33][34][35][36][37][38][39], eight were prospective and single-center [10,[40][41][42][43][44][45][46], and two were retrospective and database-registry-based [47,48]. Most commonly, LVI was defined as the unequivocal presence of tumor cells within endothelial-lined spaces.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…A total of five studies investigated the correlation between BMI and LVI [17,[25][26][27]39]. Due to substantial diversity of data presentation, one of them was excluded, leaving four studies that made the final meta-analysis [17,25,26,39]. A total of 3999 patients were analyzed, 592 of whom were LVI-positive.…”
Section: Bmimentioning
confidence: 99%